Situated Conversational Interaction (Invited Talk) - Heck, Larry; Hakkani-Tur, Dilek; Pantel, Patrick (IEEE Global Conference on Signal and Information Processing, 2013)
Robust conversational systems have the potential to revolutionize our interactions with computers. Building on decades of academic and industrial research, we now talk to our computers, phones, and entertainment systems on a daily basis. However, current technology typically limits conversational interactions to a few narrow domains/topics (e.g., weather, traffic, restaurants). Users increasingly want the ability to converse with their devices over broad web-scale content. Finding something on your PC or the web should be as simple as having a conversation. A promising approach to address this problem is situated conversational interaction. The approach leverages the situation and/or context of the conversation to improve system accuracy and effectiveness. Sources of context include visual content being displayed to the user, geo-location, prior interactions, multi-modal interactions (e.g., gesture, eye gaze), and the conversation itself. For example, while a user is reading a news article on their tablet PC, they initiate a conversation to dig deeper on a particular topic. Or a user is reading a map and wants to learn more about the history of events at mile marker 121. Or a gamer wants to interact with a game’s characters to find the next clue in their quest. All of these interactions are situated – rich context is available to the system as a source of priors/constraints on what the user is likely to say. This presentation will discuss research progress in open domain situated conversational interactions, and suggest future directions for the research community.